Abducing chances: Evolution, cognitive niches and hybrid humans as chance discoverers. (1st December 2013) - Magnani, Lorenzo
Humans continuously delegate and distribute cognitive functions to the environment to lessen their limits. They build models, representations and other various mediating structures that are considered to aid thought. In doing these, humans are engaged in a process of cognitive niche construction. In this sense, I argue that a cognitive niche emerges from a network of continuous interplays between individuals and the environment, in which people alter and modify the environment by mimetically externalizing eeting thoughts, private ideas, etc., into external supports. Through mimetic activities humans create external semiotic anchors that are the result of a process in which concepts, ideas and thoughts are projected onto external structures. Once concepts and thoughts are externalized and projected, new chances and ways of inferring come up from the blend. For cognitive niche construction may also contribute to making available a great portion of chances – in terms of information and knowledge – that otherwise would remain simply unexpressed or unreachable. The central part of this article will illustrate that abduction – or reasoning to explanatory hypotheses – is also central to understanding some features of the problem of action and decision-making. Abduction prompts new affordances and subsequent possible actions and plays a key role in decision-making, as C. S. Peirce teaches: the eco-neurological perspective depicted in this article also increases knowledge about the distinction between thought and motor action, seeing both aspects as fruit of brain activity. We can say that thought possesses an essential 'motor' component reflected in brain action but not in actual movement. On the basis of this analysis I can further illustrate some problems related to the role of abducting chances in decision-making, both in deliberate and unconscious cases.